Serum 25-hydroxyvitamin D concentrations and their impact on all-cause mortality in Parkinson’s disease: insights from National Health and Nutrition Examination Survey 1999–2020 data - Yong, Yufei; Dong, Hui; Zhou, Zhen; Zhu, Yan; Gu, Meiling; Li, Wenxiao (Frontiers in Nutrition, 2024)
Background and purpose This study explores the relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and mortality among Parkinson’s disease (PD) patients, providing evidence for the potential benefits of vitamin D (VD) supplementation. Methods PD patients were collected from the National Health and Nutrition Examination Survey (NHANES) database from 1999 to 2020. These patients were categorized based on their serum 25(OH)D levels: deficiency, insufficiency, and sufficiency. We compared demographic information and analyzed mortality data from the National Death Index. A restricted cubic spline model assessed the nonlinear association between 25(OH)D levels and mortality, complemented by multivariable Cox regression analysis. Consistency of results was checked through subgroup analysis. Results The study included 364 PD patients: 87 (23.9%) with VD deficiency, 121 (33.2%) with insufficiency, and 156 (42.9%) with sufficiency. Demographically, 46.4% were male, and 56% were over 65 years. The deficiency group predominantly consisted of Mexican Americans (53.1%), had lower income levels, a higher unmarried rate, and increased liver disease incidence. The analysis showed a U-shaped curve between 25(OH)D levels and mortality risk, with the lowest risk at 78.68 nmol/L (p-non-linear = 0.007, p-overall = 0.008). Kaplan–Meier analysis found the highest survival rates in patients with 25(OH)D levels between 75–100 nmol/L (p = 0.039). Compared to this group, patients with levels below 50 nmol/L had a 3.52-fold increased mortality risk (95% CI = 1.58–7.86, p = 0.002), and those above 100 nmol/L had a 2.92-fold increase (95% CI = 1.06–8.05, p = 0.038). Age-specific subgroup analysis (p = 0.009) revealed that both very low (<50 nmol/L) and high (>100 nmol/L) levels increased mortality risk in patients under 65, while levels below 75 nmol/L raised mortality risk in older patients. Conclusion Serum 25(OH)D levels are nonlinearly linked to mortality in PD patients, with optimal survival rates occurring at 75–100 nmol/L. Deviations from this range increase the risk of death.